Antiplasmodial activity of constituents and their metabolites after in vitro gastrointestinal biotransformation of a Nauclea pobeguinii extract. (February 2022) - Peeters, Laura; Foubert, Kenn; Baldé, Mamadou Aliou; Tuenter, Emmy; Matheeussen, An; Van Pelt, Natascha; Caljon, Guy; Hermans, Nina; Pieters, Luc
Abstract: Nauclea pobeguinii is traditionally used for treatment of malaria. Previous studies on the plant extract and strictosamide, the putative active constituent, showed a profound in vivo activity of the extract but no in vitro activity of strictosamide. This might indicate that one or more compounds present in the extract, most likely alkaloids, act as prodrugs undergoing biotransformation after oral administration resulting in the active compounds. The phytochemical composition of a N. pobeguinii extract was characterized using UHPLC-UV-HRMS (Ultrahigh-Performance Liquid Chromatography-Ultraviolet-High Resolution Mass Spectrometry) data. An in vitro gastrointestinal model was used to simulate biotransformation of the extract allowing monitoring of the relative abundances of individual constituents over time on one hand, while antiplasmodial activity and cytotoxicity of the biotransformed extract could be evaluated on the other hand. A diversity of compounds was (tentatively) identified in the extract, mainly saponins and alkaloids, including 32 compounds that have not been reported before in N. pobeguinii . The automated data analysis workflow used for unbiased screening for metabolites showed that glycosylated compounds decreased in intensity over time. Alkaloids containing no sugar moieties, including angustine-type alkaloids, showed no gastrointestinal biotransformation. In vitro gastrointestinal biotransformation of strictosamide did not result in a major metabolite. Moreover, multivariate data analysis using Orthogonal Partial Least Square-Discriminant Analysis (OPLS-DA) showed no in vitro activity of strictosamide or its metabolites suggesting that other compounds or metabolites present in the extract are responsible for the antiplasmodial effect of the N. pobeguinii extract. The OPLS-DA proposes alkaloids with a β-carboline moiety as active principles, suggesting that antiplasmodial activity of N. pobeguinii derives from an additive or synergistic effect of multiple minor alkaloids and their metabolites present in the bark extract of N. pobeguinii. Graphical abstract: Image 1 Highlights: 32 compounds are tentatively identified for the first time in N. pobeguinii extract. Glycosylated compounds showed biotransformed in an in vitro gastrointestinal model. Alkaloids without sugar moieties showed no gastrointestinal biotransformation. Strictosamide or its metabolites showed no antiplasmodial activity. Antiplasmodial activity derives from a synergistic effect of multiple compounds.